SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0994
|View full text |Cite
|
Sign up to set email alerts
|

Low Pressure-Driven Injection Characterization for SCR Applications

Abstract: A queous Urea is a non-toxic and stable ammonia carrier and its injection and mixing represent the basis for the most common de-NOx technology for mobile applications. The reactant feed preparation process is defined by evaporation, thermolysis and hydrolysis of the liquid mixture upstream the Selective Catalytic Reduction reactor, and it is strongly dependent on the interaction between spray and gaseous flow. Low-pressure driven injectors are the common industrial standard for these applications, and their be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The flash-boiling injection is particularly advantageous as it provides a high level of urea decomposition and uniform ammonia distribution [4,5]. However, those sprays are characterised by significantly smaller droplets, lower velocity and increased angles, and therefore are highly exposed to the drift [3,7,10,11,13,14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flash-boiling injection is particularly advantageous as it provides a high level of urea decomposition and uniform ammonia distribution [4,5]. However, those sprays are characterised by significantly smaller droplets, lower velocity and increased angles, and therefore are highly exposed to the drift [3,7,10,11,13,14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial double-vortex formation was observed, but surprisingly, an increase in the gas mass flow rate from 100 to 400 kg/h led to its extinction. Nocivelli et al [11] observed that the spray core composed of larger droplets was slightly affected by the crossflow (contrary to the smaller droplets), and pointed out the importance of the definition of droplet parcels in the case of the Lagrangian spray modelling approach. Another factor required for proper spray measurements is a stable flow.…”
Section: Introductionmentioning
confidence: 99%